2020
DOI: 10.1016/j.psj.2019.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of housing system and age on products and bone properties of Taihang chickens

Abstract: The aim of this study was to compare egg quality, carcass, meat characteristics, and bone properties of Taihang chickens in 2 different housing systems at various ages. A total of 168 birds were selected and randomly allocated to 2 groups at 23 wks and raised in conventional cage ( CC ) or flattening on floor ( FF ) housing system, respectively. FF hens' egg weight, albumen height, and Haugh unit were higher ( P < 0.05), and yolk weight was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…In terms of the external egg quality, the egg weight ( EW ) of the local breeds, including Taihang (pink- and blue-shelled) and Dongxiang, were approximately 50 g, which were significantly lower than those of the pure lines and commercial strains ( P < 0.05). The egg weight is positively correlated with the body weight; thus, the lower egg weight of the local breeds may have been due to the lower body weight ( Liao et al, 2016 ; Yue et al, 2020 ). The differences in appearance of the eggshells are shown in Figure 1 , and there were 4 eggshell colors, namely, brown, pink, white, and blue.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the external egg quality, the egg weight ( EW ) of the local breeds, including Taihang (pink- and blue-shelled) and Dongxiang, were approximately 50 g, which were significantly lower than those of the pure lines and commercial strains ( P < 0.05). The egg weight is positively correlated with the body weight; thus, the lower egg weight of the local breeds may have been due to the lower body weight ( Liao et al, 2016 ; Yue et al, 2020 ). The differences in appearance of the eggshells are shown in Figure 1 , and there were 4 eggshell colors, namely, brown, pink, white, and blue.…”
Section: Resultsmentioning
confidence: 99%
“…Fractures of keel bones are a real problem in rearing systems of intensive laying hens [32]. There were also found to be differences in fracture toughness due to higher movement in tibia bones of hens that were housed in flat floors (these hens had bones more resistant to fracture) than of hens in cages [11]. Results of these studies should mean that ducks that will have a greater ability to move will also have bones that are more resistant to fracture.…”
Section: Bone Qualitymentioning
confidence: 98%
“…Another factor that influences the well-being of animals, is bone quality, which can be affected by movement. In the study of [11], it was found that hens that were housed in floor systems with an increased possibility of movement had higher fracture toughness than hens in cages. In addition, the importance of the gender effect should not be overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Our data are agreement with [25] who reported that egg weight increases with hen age advanced. Moreover, [26] found that the percent of yolk differ significantly between different ages and as the age advances the yolk weight increase in the egg. In addition, Rayan 2018 pointed that the egg shell weight, albumen high and HU were significantly decreased in a stepwise manner with increased parental age.…”
Section: Egg Compositionmentioning
confidence: 99%